Konsep Kendiri Murid Di Sekolah Bandar Dan Luar Bandar, Sekitar Daerah Limbang, Sarawak - Yahya, Yusairy (2015)

(untitled)
The purpose of this study was to observe self-concept pupil. In spite of that, the study was also to observe the self-concept pupil by two demography factors that are sex and location. This study also revel the different self-concept by sex and location. This study used survey method. Data was collected quantitatively through the distribution of questionnaires The Tennesse Self-Concept Scale (l'SCS) to 148 respondents. The result of study showed, no significant min difference self-concept among male and female pupil on value t (-.182) = .856, P >.05. However, the result showed that significant min self-concept among pupil in town and in village on value t (5.072) = .000, p <.05. It can be concluded all people should responsible to improve selfconcept pupil in town and village